PERAN ORGANIZATION FOR ECONOMIC COOPERATION AND DEVELOPMENT (OECD) MEMFASILITASI KESEPAKATAN PAJAK DIGITAL ANTARA PRANCIS DAN AMERIKA SERIKAT - ,, Sasriaini; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the role of the Organisation for Economic Co-operation and Development (OECD) in facilitating a digital tax agreement between France and the United States in response to the dispute arising from the implementation of the Digital Services Tax (DST). France introduced the DST in 2019 to impose taxes on revenues earned by foreign digital companies that profit from users within its jurisdiction without having a physical presence. This policy sparked strong opposition from the United States, which viewed it as discriminatory against major U.S. technology firms such as Google, Apple, Facebook, and Amazon. This research uses a qualitative method with data collected through literature studies sourced from books, journals, articles, and official websites. The study applies the Neoliberalist perspective and the theory of international organization as proposed by David Lewis. The findings indicate that the OECD plays a vital role as an international actor not only by providing a negotiation platform but also by designing multilateral solutions through the Base Erosion and Profit Shifting (BEPS) project. Through the Inclusive Framework, the OECD developed a global digital tax reform scheme based on a Two-Pillar Approach. Pillar One, particularly Amount A, serves as a mechanism to allocate taxing rights across jurisdictions based on user location, aiming to replace unilateral measures such as the DST. The OECD successfully mediated a compromise between France and the United States involving the suspension of DST and the withdrawal of trade sanctions, under the condition that DST would be repealed following the implementation of Pillar One through a Multilateral Convention. Keywords: OECD, Digital Services Tax, Amount A, BEPS, Pillar One